Utilization of Sentinel-2 Imagery for Water Quality Analysis: A Case Study of Saguling Reservoir - Ruuhulhaq, Muhammad Saiful; Setianingrum, Sarah (Amcolabora, 2025)
Water resources are essential for human life and are one of the main indicators of regional development success. Saguling Reservoir is one of the reservoirs located in West Java that plays a crucial role in various aspects of the lives of the surrounding community. This study aims to determine the distribution of Total Suspended Solids in Saguling Reservoir and to assess turbidity levels using the Normalized Difference Turbidity Index. This study utilizes the Total Suspended Solids (TSS) model by Huizeng Liu using Sentinel-2 imagery data. Based on the research findings, Saguling Reservoir has three classes of Total Suspended Solids (TSS): low (902.91 hectares), moderate (1830.47 hectares), and high (592.78 hectares). Meanwhile, the turbidity levels in Saguling Reservoir are very low (212.84 hectares), moderate (2649.94 hectares), and high (457 hectares).